Identification Types of Waste in Panties Production at PT Indonesia Wacoal - Putri Dewi Larasati , Ajeng; Rimantho, Dino (Journal Knowledge Industrial Engineering (JKIE), 2023)
PT Indonesia Wacoal is a garment company that produces underwear with several product variations: panties. Companies must always produce good quality products by maximizing production results and high productivity. However, waste becomes an obstacle to the company's performance in carrying out its production. The potential for the emergence of waste can occur in all company activities, where PT Indonesia Wacoal experienced the same thing. This study aims to identify and analyze waste that occurs in the production process of panties. The waste is defective products, transportation, excessive movement, and waiting time. The method used in this article is seven tools: the Pareto diagram and the fishbone diagram. The identification results indicate that the waste of defective products in Wolly yarn is about 211 seconds or 64.04%. In addition, there is a long process of transferring material from QC to the finished product warehouse of around 1188 seconds or 29.73%. Furthermore, excessive movement in the sewing process for 2340 seconds or 45.14% and waste due to the waiting time for the storage process to the next process is 4320 seconds or 42.40%. The identification results show several factors causing waste such as labor, machines, methods, materials and the environment.